PrEP use and unmet PrEP-need among men who have sex with men in London prior to the implementation of a national PrEP programme, a cross-sectional study from June to August 2019 - Dana Ogaz; Louise Logan; Tyrone J. Curtis; Lorraine McDonagh; Luis Guerra; Daniel Bradshaw; Poorvi Patel; Chiara Macri; Gary Murphy; O. Noel Gill; Anne M. Johnson; Anthony Nardone; et al. (BMC, 2022)
Abstract Background Access to prevention options, including HIV pre-exposure prophylaxis (PrEP), remains a public health priority for gay, bisexual, and other men who have sex with men (MSM), especially in London. We describe PrEP use in a London community sample of MSM before the introduction of a national PrEP programme in October 2020. Methods From June-August 2019, MSM aged ≥ 18 recruited from London commercial venues were asked to self-complete a sexual health questionnaire and provide an oral fluid sample for anonymous HIV antibody testing. Descriptive analyses of demographic characteristics, service engagement and outcomes, as well as sexual risk and prevention behaviours were examined in the survey population and in those reporting current PrEP use. We performed sequential, multivariate analyses examining current PrEP use in MSM of self-perceived HIV-negative/unknown status with identified PrEP-need defined as the report of condomless anal sex (CAS) in the last three months, or the report of CAS (in the last year) with an HIV-positive/unknown status partner not known to be on HIV treatment, in reflection of UK PrEP guidelines. Results One thousand five hundred and thirty-fifth questionnaires were completed across 34 venues, where 1408 were analysed. One in five MSM of self-perceived HIV-negative/unknown status reported current PrEP use (19.7%, 242/1230). In men with PrEP-need, 68.2% (431/632) did not report current use. Current PrEP use was associated with age (aOR: 3.52, 95% CI: 1.76-7.02 in men aged 40-44 vs men aged 18-25) and education (aOR: 1.72, 95% CI: 1.01-2.92 in men with ≥ 2 years/still full-time vs no/ < 2 years of education since age 16). Conclusion Among MSM in London, PrEP use is high but there is indication of unmet PrEP-need in men of younger age and lower levels of post-16 education. National programme monitoring and evaluation will require continued community monitoring to guide interventions ensuring equitable PrEP access and uptake in those who could most benefit from PrEP.